Ivacaftor treatment of cystic fibrosis patients with the G551D mutation: a review of the evidence. (October 2013) - Kotha, Kavitha; Clancy, John P.
Cystic fibrosis (CF) is a recessive disorder caused by mutations in the gene that encodes the CF transmembrane conductance regulator (CFTR) protein. CFTR protein is a chloride and bicarbonate channel that is critical for normal epithelial ion transport and hydration of epithelial surfaces. Current CF care is supportive, but recent breakthroughs have occurred with the advent of novel therapeutic strategies that assist the function of mutant CFTR proteins. The development and key clinical trial results of ivacaftor, a small molecule that targets gating defects in disease-causing CFTR mutations including G551D CFTR, are summarized in this review. The G551D mutation is reasonably common in the CF patient population and produces a CFTR protein that localizes normally to the plasma membrane, but fails to open in response to cellular cues. Ivacaftor treatment produces dramatic improvements in lung function, weight, lung disease stability, patient-reported outcomes, and CFTR biomarkers in patients with CF harboring the G551D CFTR mutation compared with placebo controls and patients with two copies of the common F508del CFTR mutation. The unprecedented success of ivacaftor treatment for the G551D CF patient population has generated excitement in the CF care community regarding the expansion of its use to other CF patient populations with primary or secondary gating defects.